Rational cognition: historical-philosophical retrospective - Alexeychuk, Ihor S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
In the article the historical-philosophical aspect of the problem of rational cognition has been analyzed. It has been proved that antique tradition divides senses, common sense and reason. This tradition was developed in the works of I. Kant and G. Hegel. To the middle of ХХ century in philosophy and science was acknowledged division into sensual and rational cognition. There are different kinds of interpretation of cognition have been investigated. Special attention has been paid to the five groups of conceptions of the truth: classic, pragmatic, conventional, hermeneutic and dialecticalmaterialistic. The main historical paradigms of views on sense have been described. It was concluded that criticism of Modern and philosophical tradition of the New Age helped in deeper understanding of the main paradigms of classical thinking: logocentrism, structure of being, fundamentalism and traditional conception of representation.